Penggunaan Al-Qur’an dan Hadis di Balik Komersialisasi Thibbun Nabawi di Media Sosial - Munirah Munirah (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2023)
Thibbun Nabawi or also called the Treatment of the Prophet has an attraction especially when Covid-19 appears. This provides a great opportunity for entrepreneurs to be involved in this Nabawi Thibbun Nabawi business, especially in Indonesia with the majority Muslim community. The marketing is even easier with the help of social media. Various kinds of strategies are carried out to promote the products sold including using the Qur'an and Hadith verses. In this case, the Qur'an and hadith are used for certain purposes outside of their functions. To uncover this phenomenon I explores data from Instagram social media. The results of this study are: 1) Nabawi Thibbun Products which are most often promoted with verses of the Qur'an and Hadith in Instragram are honey and habbatussauda’, 2) The use of verses of the Qur'an and hadith behind this phenomenon is included in Islamic marketing which functions as a promotion and communication strategy as well as a da'wah platform and economic improvement. In addition to selling merchandise, behind the use of the Qur'an and hadith there are efforts to broadcast and revive the teachings of the Qur'an and hadith, especially in maintaining health and medicine. 3) there is the power of well-known religious leaders as brand ambassadors for Thibbun Nabawi who seek to introduce the concept of healthy living and the method of treatment by the Prophet